2022
DOI: 10.2514/1.j061106
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Turbulence Spectrum Dissipation Range for Leading-Edge Noise Prediction

Abstract: Noise pollution caused by inflow turbulence is a major problem in many applications, e.g., propellers and fans. The Amiet leading-edge noise prediction model is widely applied in the design of silent propellers and fans, strongly relying on the accuracy of the inflow turbulence spectrum. The von Kármán energy spectrum accurately models the energy-containing range and inertial subrange of the turbulence spectrum. However, this model does not incorporate the dissipation range of the turbulent energy and leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Two-component hot-wire measurements of turbulence quantities, spectra, and space-time correlations were performed for the grid without the airfoil in the flow. These measurements were discussed in [36]. These measurements showed that the turbulent flow is isotropic with a spectral form accurately described by the von Kármán turbulence spectrum.…”
Section: Inflow Turbulencementioning
confidence: 94%
See 4 more Smart Citations
“…Two-component hot-wire measurements of turbulence quantities, spectra, and space-time correlations were performed for the grid without the airfoil in the flow. These measurements were discussed in [36]. These measurements showed that the turbulent flow is isotropic with a spectral form accurately described by the von Kármán turbulence spectrum.…”
Section: Inflow Turbulencementioning
confidence: 94%
“…and 𝑓 𝜂 is a formulation to model the dissipation range for high frequencies and 𝜂 is the Kolmogorov length scale. Dos Santos [36] proposed an empirical relation to model this term, see [36, pp. 8], and a formulation to compute the Kolmogorov length scale from turbulence parameters considering an isotropic turbulence [36, pp.…”
Section: Amiet's Leading-edge Noise Prediction Modelmentioning
confidence: 99%
See 3 more Smart Citations